A three-dimensional particle method for violent sloshing under regular and irregular excitations. (1st July 2016) - Luo, M.; Koh, C.G.; Bai, W.
Abstract: A three-dimensional (3D) numerical model is presented in the framework of Consistent Particle Method (CPM). The 3D gradient and Laplacian operators are derived based on Taylor series expansion, achieving good accuracy and largely alleviating the problem of spurious pressure fluctuation. An accurate boundary recognition scheme is introduced to determine the highly deformed free surface. Validated by our experimental studies of water sloshing under translational and rotational excitations, this model is shown to be robust and accurate in long time simulation of violent free surface flows which involve fluid merging and splitting. Using the validated numerical model, liquefied natural gas sloshing in a real ship under sea excitations is investigated. It is found that the sloshing waves in the beam sea sailing condition is the most violent and seriously affects the stability of ship motion. Various wave patterns under different excitations are discussed. Highlights: A three-dimensional (3D) particle model is developed for violent free surface flows. New gradient and Laplacian operators are formulated based on Taylor series expansion. A new free-surface recognition scheme is proposed for violent 3D free-surface problems. Experimental studies of water sloshing under different excitations are conducted for validation. A practical example of liquefied natural gas sloshing under sea excitations is demonstrated.